S-index periodicity detection based on multiple random spectral observations - Shen, Yu-Fu (Scientific reports, 2023)
The solar magnetic activity cycle has a profound impact on our lives, yet its underlying causes remain elusive. While similar cycles have been observed in other stars, these results are scarce due to the significant challenge posed by the length of time required for observation. Continuous observation over an extended period is a luxury, making it difficult to gather large samples. However, multiple random observations can be made at a lower cost, and flexible time management enables non-professionals to become competent. In this study, we analyzed multiple random observations of the S-indices of several stars captured incidentally by the Large Sky Area Multi-Object Fiber Spectroscopic Telescope. Our findings reveal potential periodicity that could be associated with magnetic activity cycles. Notably, obtaining S-index is relatively less challenging, indicating the feasibility of developing dedicated commercial or charitable equipment for non-astronomers. A more extensive data is essential to establish a definitive correlation between S-index periodicity and magnetic activity cycles in stars, as well as to uncover additional magnetic activity cycles.